Simone Weil and the need for obedience: political, religious, and ethical dimensions - Lawson-Frost, Sasha (Labyrinth, 2024)
This essay explores the development of Simone Weil's conception of obedience across religious, political, and ethical contexts. By bringing together these strands of Weil's thought, it aims to illuminate some important connections in her treatment of obedience throughout these diverse topics. The author argues that Weil's political treatment of obedience is deeply influenced by ideas in Christian thought, and that this account is situated within an understanding of obedience in the natural world which is itself ethically loaded. Hence it is suggested that Weil's account of obedience has something to offer philosophy today: namely, a conception of obedience which recognises the practical and ethical need for obeying others, but which is distinct from the mere submission to power.